Atsār Al-Azmah Al-Khalījiyyah ‘alā Al-Āmal Al-Insāniy Al-Qathariy - Ghassan Elkahlout (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2018)
The Gulf crisis, which broke out on June 5, 2017 between Qatar and the four countries (Saudi Arabia, the UAE, Egypt and Bahrain), surprised the world. The four countries initiated punitive action against Qatar and justified it in seeking to stop Qatar from supporting terrorism. The sanctions included a diplomatic boycott, an economic blockade and an air embargo, amounting to the criminalization of sympathizers of the four countries' nationals with Qatar. The Qatari humanitarian sector was one of the targeted sectors in the crisis. The four countries launched smearing campaigns against the Qatari humanitarian work in regional and international forums. The article describes how the Gulf crisis has affected the humanitarian landscape in Qatar. It elaborates on the impact on actors such as donors, humanitarian workers, partnerships and the level of international Qatari cooperationDOI: 10.15408/insaniyat.v2i2.8031